PENGARUH PENYALURAN KREDIT, BIAYA DANA BANK, DAN KREDIT BERMASALAH TERHADAP RENTABILITAS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI TAHUN 2010-2012 (Students' Journal of Accounting and Banking, 2014)
This study aimed to analyze the effects of loans, the Cost Of Funds, and non performing loans to profitability in banking companies listed in Indonesia Stock Exchange in 2010-2012. Profitability is important for banks because it is used to measure the capacity of the company to profit through all the existing capabilities and resources. The population in this study is a banking company that is listed on the Indonesia Stock Exchange in 2010 to 2012. Samples were taken by using purposive sampling method, so it can be obtained a total 83sample. The data analysis method used is multiple linear regression analysis which is using the SPSS tool. The study results showed that the variables of loans have the a significant positive effect on profitability, while the cost of funds and non performing loans have no effect on profitability. For loans, cost of funds, and non performing loans together have influence on profitability.Keywords: Profitability, Loans, Cost Of Fund, Non Performing Loans